FLOW RESISTANCE IN OPEN CHANNEL FLOWS WITH SPARSELY DISTRIBUTED BUSHES - Righetti M.; Armanini A. (My University, 2002)
The paper faces the problem of the resistance due to vegetation in a river characterized by fully submerged vegetation formed by concentrated colonies of bushes. The flow presents strong spatial variations between plants that make unreliable the traditional approach based on time averaging of turbulent fluctuations. A more useful model, based on time and spatial averaging is proposed. In the paper the necessary closure hypotheses are also discussed. The vertical distribution of mean velocity and turbulence stress have been measured with laser Doppler anemometry techniques, by means of spatial and time-averaging rules. Based on the double-averaged velocity and Reynolds stress profiles, an analytical two-layer model is proposed, in order to describe uniform flow conditions in the whole flow depth. Theoretical results are compared with the results of a series of experimental tests carried out in a laboratory flume.
Keywords: VEGETATED CHANNELS, TURBULENCE MODEL; LASER DOPPLER ANEMOMETRY